Need to increase the career of Metallurgical Engineering in Peruvian universities - Asencios Trujillo, Lida Violeta (2019)
In the following article, two fundamental elements are analyzed: the mining situation in Peru, and the need to increase Metallurgical Engineering studies. Both elements must be inextricably linked, as they respond to economic and social needs that are increasingly accentuated. The work is articulated in several sections that begin with a brief historical analysis of the role of education and social development, where the role of universities in this area is insisted. Comparisons of the above are also offered with other countries, both within the area and globally, to reach the following objective: provide necessary information to raise awareness of the urgency of extending and perfecting the university studies of Mining Engineering in the national environment. On the other hand, emphasis is placed on the social conflicts that unfortunately originate and remain in the mining-related population. For this purpose, some elements contributed by the master's thesis Meeting paths in the management of social conflicts were taken as a basis the mining sector: Cocachacra case.